Quality of Life and its Relation to the Level Physical Activity and sport in a Sample of Damascus University Students (Damascus University Journal of educational and Psychologyical sciences, 2021)
The study aimed to distinguish the level of quality of life (QOL) and identify its relation with the level of physical activity in Damascus university students according to gender and classifications of physical activity level. In addition, it aimed to recognize the differences between QOL of them. The descriptive analytic methodology was used and a total of 243 students participated in the study voluntarily, of whom 128 females and 115 males. Mansi and Kathem (2006) QOL scale was  used for the assessment of QOL, and the short form of the international physical activity questionnaire (IPAQ brief) for the assessment of physical activity level. Results indicated that the QOL of university students was low, and significant differences were found between males and females in general health-, emotions-, and psychological health subsets only in favor of males. The percentage of total inactive males was 36.6% and for females was 46.50%.The relationship between QOL and level of physical activity was progressively positive (r=0.86), where the higher scores of PA indicate higher level of QOL.
Keywords: Life Quality; Level of Physical Activity; Damascus University Students.